2020
DOI: 10.11648/j.eeb.20200501.12
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder Tobacco Farmers and Forest Conservation in Mutasa District, Zimbabwe

Abstract: Zimbabwe is among the poorest countries in the world and heavily depends on agriculture for rural livelihoods and income generation. Forests conversion into agricultural land and the use of forest products, in particular fuel wood for the construction of tobacco barns and the curing process has caused destruction to the already depleted forests. The study was carried out in Mutasa District in the eastern highlands, Zimbabwe. Quantitative and qualitative data techniques were used in the study. A total of 60 sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…Our results agree with Waluye (1994) study, which reported that Urambo district farmers often move distance to harvest wood fuel for tobacco curing. Also, our findings are in agreement with the study by Lawrence et al (2020) who found that many forest woodlands near the homestead have been cleared than those far from the homestead. This results in increases in the wood fuel cost.…”
Section: Economic Aspects Of Tobacco Curingsupporting
confidence: 93%
“…Our results agree with Waluye (1994) study, which reported that Urambo district farmers often move distance to harvest wood fuel for tobacco curing. Also, our findings are in agreement with the study by Lawrence et al (2020) who found that many forest woodlands near the homestead have been cleared than those far from the homestead. This results in increases in the wood fuel cost.…”
Section: Economic Aspects Of Tobacco Curingsupporting
confidence: 93%
“…The participants opine that they use wood fuel for cooking, warming and lighting their houses. The study area is rich in miombo woodlands which support different livelihood outcomes [66]. Trees that provide source of energy and fruits included a mixture of Brachystegia spiciformis, Jubenardia globorora, Brachystegia boehmii, Brachystegia tamarinodoide and Uapaca kirkianaand [67].…”
Section: Agroforestry and Related Activitiesmentioning
confidence: 99%
“…The Government of Zimbabwe, through TIMB, EMA, and Forestry Commission, together with tobacco companies, have introduced various strategies or measures to mitigate the tobacco production effects on the environment through deforestation (TIMB, 2015). Gum plantation is one of the possible solutions recommended to promote the regeneration of depleting forests (Saccheto, 2012;TIMB, 2016;Lawrence et al, 2020;Matiashe, 2022). The FCZ launched the Tobacco Wood Energy Program (TWEP) in 2005 in an attempt to curb the challenges of deforestation by encouraging smallholders to establish woodlots.…”
Section: Introductionmentioning
confidence: 99%
“…According to Munanga et al, (2014), a significant number of farmers transitioned from the use of coal to wood fuel due to the cost and unavailability of electricity as well as the collapse of the railway system in Zimbabwe. A study by Lawrence et al, (2020) recommended the government and tobacco companies provide coal to tobacco farmers at a subsidized price to encourage its adoption by smallholders, thereby reducing deforestation. According to Saccheto (2012), coal has been used as a common alternative to wood for flue-curing in China.…”
Section: Introductionmentioning
confidence: 99%